Four new species of Rhyacophila Pictet, 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia - Suwannarat, Nannaphat; Malicky, Hans; Morse, John C.; Laudee, Pongsak (Zootaxa, 2019)
Four new species of genus Rhyacophila are described and illustrated from Thailand and Myanmar, Southeast Asia. Rhyacophila longicaudata sp. n. is in the R. nigrocephala Group; the very long basal segment of each inferior appendage distinguishes it from other related species. Rhyacophila aksornkoaei sp. n. and R. limsakuli sp. n. are in the R. anatina Group: they can be differentiated from other species of the group by the brush-like parameres and presence of a ventral process of the aedeagus in R. aksornkoaei sp. n., and by the rectangular apical segment of each inferior appendage and the hooked parameres in R. limsakuli sp. n.. Rhyacophila kengtungensis is in the R. yishepa Group and is characterized by the subtriangular shape of the preanal appendages in dorsal view and by the very large dorsal appendages of the phallic apparatus.